Generation of conditional null alleles for APP and APLP2 - Mallm, Jan-Philipp; Tschäpe, Jakob-Andreas; Hick, Meike; Filippov, Mikhail A.; Müller, Ulrike C. (Genesis, 2010)
Proteolytical cleavage of the β-amyloid precursor protein (APP) generates β-amyloid, which is deposited in the brains of patients suffering from Alzheimer's disease (AD). Despite the well-established key role of APP for AD pathogenesis, the physiological function of APP and its close homologues APLP1 and APLP2 remains poorly understood. Previously, we generated APP-/- mice that proved viable, whereas APP-/-APLP2-/- mice and triple knockouts died shortly after birth, likely due to deficits of neuromuscular synaptic transmission. Here, we generated conditional knockout alleles for both APP and APLP2 in which the promoter and exon1 were flanked by loxP sites. No differences in expression were detectable between wt and floxed alleles, whereas null alleles were obtained upon crossing with Cre-transgenic deleter mice. These mice will now allow for tissue and time-point controlled knockout of both genes. genesis 48:200-206, 2010. © 2010 Wiley-Liss, Inc.
Gesehen am 03.05.2023